Environmental impact on male reproductive function: focusing on a canine sentinel - Sumner, Rebecca (2017)
Over the last three decades, there has been increasing concern over environmental effects on human male reproductive health. Both temporal and regional trends in semen quality, testicular cancer and malformations at birth have been associated with changes or differences in exposure to chemicals present within the environment. These abnormalities are typically classified under one entity, Testicular Dysgenesis Syndrome [TDS]. Since temporal trends in sperm quality have also been reported in the dog, it was proposed that this may reflect a common cross-species environmental aetiology and that the dog is a sentinel for human exposure to ECs. The overarching hypothesis of this thesis is that the dog may exhibit regional differences symptomatic of TDS and may respond to environmental influences in a similar manner to the human. Experimental studies designed to test this hypothesis focused on (1) the sensitivity of sperm to environmental influences, (2) canine sentinel testicular chemical profiles and pathological features of testes from specific geographical regions and (3) possible environmental influences impacting on cryptorchidism in dogs. Humans and animals are not directly exposed to single chemicals but to a mixture of environmental toxicants present within the environment. Chapter 3 initiated investigations into mixture effects of ECs by utilising a novel full factorial chemical model of two chemicals known to be present in reproductive tissues. Concentrations of di (2-ethylhexyl) phthalate [DEHP] and polychlorinated biphenyl congener 153 [PCB-153] at environmentally relevant levels, as determined by testicular chemical profiling of dog testes, and their effects upon parameters of sperm quality, were tested in vitro. While subtle differences in motility were observed between species, DNA fragmentation was increased similarly in both the human and dog following EC exposure. Although this applied to individual and mixed chemicals, the effects of one chemical impacted on the activity of the other dependent on the concentration ratio. Interestingly, for DNA fragmentation, data presented suggests that PCB-153 is the driver behind increased sperm DNA damage in both species. Since the data alluded to above support the concept of utilising the domestic dog as a sentinel for human exposure to ECs, the dog was used to investigate regional variation upon testicular developmental, morphological and histopathological features. The regions selected for in this component of the thesis display different degrees of industrialisation and thus variation in exposure to environmental contaminants. Data presented demonstrate significant regional variation in chemical profiles, testicular developmental markers and histopathological features indicative of TDS. Specifically, testicular DEHP and PCB-153 with known geographical variation, were found to be positively associated with markers of proliferation and spermatogenesis. Interestingly, a further chemical present in dog testis, poly-brominated diphenyl ether congener 47 [PBDE-47], was negatively correlated with these markers. Furthermore, a novel system developed to assess and score histopathological abnormalities in testes, revealed a higher range of atypical features in testes from the UK compared to those collected from Scandinavia. A further novel element of this thesis was the development of a survey to assess environmental influences on cryptorchidism across several breeds of dog. Uniquely, a higher prevalence of cryptorchidism was observed in deerhounds originating from the East Midlands. Of the range of environmental influences investigated, a key observation was that some bitches of cryptorchid pups were fed a specific brand of feed previously reported to contain ECs. Assessment of further environmental factors covered by the survey such as exposure to pesticides, cigarette smoke and air fresheners provided preliminary information pending the further repeat release of the survey to the same breeders in future years. These data provide preliminary evidence into possible environmental factors that could influence canine and human reproductive health. In conclusion, the results presented in this thesis are significant since they add considerable weight to the paradigm that environmental factors impact directly on male reproductive function. Unique data presented within this thesis emphasises that specific chemical types perturb sperm function and these chemicals vary by region. Furthermore, the work presented here consolidate the suitability of the domestic dog as a sentinel for human exposure to contaminants thus providing the added benefit of enabling access to reproductive tissues from different regions as an index of human reproductive health.